2007
DOI: 10.1590/s0001-37652007000200014
|View full text |Cite
|
Sign up to set email alerts
|

Past and current sediment dispersion pattern estimates through numerical modeling of wave climate: an example of the Holocene delta of the Doce River, Espírito Santo, Brazil

Abstract: This paper presents a numerical modeling estimation of the sediment dispersion patterns caused by waves inciding through four distinct coastline contours of the delta plain of the Doce River during the Late Holocene. For this, a wave climate model based on the construction of wave refraction diagrams, as a function of current boundary conditions, was defi ned and was assumed to be valid for the four coastlines. The numerical modeling was carried out on basis of the refraction diagrams, taking into account the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 7 publications
0
12
0
6
Order By: Relevance
“…It should be noted that the 30 m water depth represents the depth of bed remobilization by most frequent storm waves, which in the region have a significant height of 1.5 m and peak period of 6.5 s (Bittencourt et al 2007). Another indication of this process is the higher bulk density values northwards (Figs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It should be noted that the 30 m water depth represents the depth of bed remobilization by most frequent storm waves, which in the region have a significant height of 1.5 m and peak period of 6.5 s (Bittencourt et al 2007). Another indication of this process is the higher bulk density values northwards (Figs.…”
Section: Discussionmentioning
confidence: 97%
“…During cold front periods, higher energy waves from the S and SSE quadrant with higher wave orbital velocities could remobilize and transport fine sediments northward (Bittencourt et al 2007). It should be noted that the 30 m water depth represents the depth of bed remobilization by most frequent storm waves, which in the region have a significant height of 1.5 m and peak period of 6.5 s (Bittencourt et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…J.K. Guimarães and J.M.L. Dominguez (unpublished data) and Bittencourt et al (2007a) used the same method utilized by Bittencourt et al (2005) and the current boundary conditions to estimate via inverse numerical modeling the patterns of net longshore drift under different scenarios during the quaternary evolution of the São Francisco River delta (in the central part of the east-northeastern Brazilian coast) and Doce River delta (in the south part of the east-northeastern Brazilian coast), observing that these patterns were comparable to those estimated from paleogeographical reconstructions. Subsequently, Bittencourt et al (2007b) used a similar approach in the São Francisco River mouth to explain the different erosive phases that historically have been occurring there.…”
Section: Introductionmentioning
confidence: 83%
“…Therein, the Jequitinhonha River delta plain was studied (state of Bahia) (Fig. 1), whose development during the Late Holocene (Dominguez et al 1987(Dominguez et al , 2009) has shown evolutionary particularities that are distinct from those of the Doce River, which has been studied by Bittencourt et al (2007a). Dominguez et al (1987Dominguez et al ( , 2009 have shown that the coastal plain associated with the Jequitinhonha River mouth is bounded by ancient cliffs carved in Miocene age deposits of the Barreiras Formation (Suguio and Nogueira 1999).…”
Section: Introductionmentioning
confidence: 99%
“…mação, de células dos sentidos da deriva efetiva de sedimentos ao longo da região costeira leste-nordeste brasileira à partir de modelos conceituais (Dominguez et al 1992, Dominguez & Bittencourt 1996, Martin et al 1998) e numéricos (Silva et al 2001, Diniz 2002, Neves 2003, Oliveira 2003, Bittencourt et al 2000, 2005, 2007ae b, Guimarães & Dominguez 2005, Nascimento et al 2007 sugere que, em média, as condições de contorno atuais (ventos e ondas) parecem ter permanecido com as mesmas características gerais desde o Quaternário Tardio (120.000 A.P. ), como apontado por Dominguez et al (1992) …”
unclassified